HUBUNGAN KONSUMSI TABLET FE DENGAN KADAR HB PADA REMAJA PUTRI - DEWI APRILIA NINGSIH. I (STIKes CHMK, 2020)
The prevalence of anemia in adolescent girls is still high at 26.50%, while the coverage of giving Fe tablets consumed by 1.4%, whereas in Bengkulu province in 2018 only 35.1% or 72,685 people got Fe tablets. This study aims to determine the relationship of consumption of Fe tablets with Hb levels in Young Women. This type of research is an analytic survey with cross sectional approach. The population in this study were all VII and VIII grade students of SMPN 19 Bengkulu City in March 2019, totaling 245 people. Samples were taken using a cluster sampling technique of 71 people. Data collection uses primary data by interviewing and distributing questionnaires and observing HB levels. Data analysis using chi-square test. There is a relationship between the consumption of Fe tablets with hemoglobin levels in adolescent girls class VII and VIII at SMPN 19 Bengkulu City with a strong relationship category. It is expected that the school can organize a CIE program on nutrition and health in adolescents in collaboration with health workers, as well as in collaboration with parents of students to supervise and control the consumption of Fe tablets to young women.